2020
DOI: 10.36760/jp.v1i2.91
|View full text |Cite
|
Sign up to set email alerts
|

PENGEMBANGAN NANOPARTIKEL EKSTRAK DAUN KERSEN(Muntingia calabura.L) DENGAN TEKNIK SELF NANO EMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) UNTUK APLIKASI ANTIBAKTERI

Abstract: Kandungan flavonoid dan tanin pada daun kersen dapat  menghambat pertumbuhan bakteri Staphylococcus aureus. Penelitian ini bertujuan untuk mengetahui pengaruh formulasi nanoemulsi daun kersen (Mutingia calabura.L) terhadap karakteristik nanoemulsi menggunakan teknik Self Nano Emulsifying Drug Delivery System (SNEDDS) dan  pengaruhnya sebagai antibakteri Staphylococcus aureus. Ekstrak etanol daun kersen diformulasi dengan surfaktan, kosurfaktan dan minyak terpilih. Kemudian nanoemulsi ekstrak daun kersen diuji … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…This study refers to the best formula from three studies, namely the research of [17] with the title of formulation, characterization and evaluation of the Self-Nano Emulsifying Drug Delivery System (SNEDDS) ethanol extract of pineapple peel as an antibacterial Streptococcus mutans, [12] entitled Optimization of Tween 80 and Polyethylene Glycol 400 in Self-Nanoemulsifying Drug Delivery System (SNEDDS) Basil (Ocimum basilicum) Leaf Essential Oil Nanoemulsifiying Drug Delivery System (SNEDDS) Basil Essential Oil (Ocimum basilicum) and research by [16] with the title Development of Kersen Leaf Extract Nanoparticles (Muntingia calabura L.) with Self Nano Emulsifying Drug Delivery System (SNEDDS) Technique for Antibacterial Applications. Researchers will compare the best formulas from the three studies and use the active substance of the n-Hexane: ethyl acetate fraction of Sesewanua leaves (Clerodendrum fragrans Wild.)…”
Section: Snedds Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…This study refers to the best formula from three studies, namely the research of [17] with the title of formulation, characterization and evaluation of the Self-Nano Emulsifying Drug Delivery System (SNEDDS) ethanol extract of pineapple peel as an antibacterial Streptococcus mutans, [12] entitled Optimization of Tween 80 and Polyethylene Glycol 400 in Self-Nanoemulsifying Drug Delivery System (SNEDDS) Basil (Ocimum basilicum) Leaf Essential Oil Nanoemulsifiying Drug Delivery System (SNEDDS) Basil Essential Oil (Ocimum basilicum) and research by [16] with the title Development of Kersen Leaf Extract Nanoparticles (Muntingia calabura L.) with Self Nano Emulsifying Drug Delivery System (SNEDDS) Technique for Antibacterial Applications. Researchers will compare the best formulas from the three studies and use the active substance of the n-Hexane: ethyl acetate fraction of Sesewanua leaves (Clerodendrum fragrans Wild.)…”
Section: Snedds Preparationmentioning
confidence: 99%
“…Based on the results of research by [16], showed that the concentration of Tween 80 as a surfactant and PEG 400 as a cosurfactant (6:3) had a particle size of 12.4 nm, zeta potential 30.8 mV, nano emulsified time 49.55 seconds and percent transmittance 97.7%. Another study from [12], succeeded in showing the concentration of Tween 80 and PEG 400 (7:2) having a particle size of 46.1 nm, zeta potential 0.46 mV, emulsification time of 47.44 seconds, and percent transmittance 99.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Kemudian dilakukan pencampuran menggunakan magnetic stirrer pada suhu 40˚C selama 10 menit [6]. Kemudian dioptimalkan dengan alat sonikator selama 15 menit dengan tujuan memaksimalkan proses pelarutan [7].…”
Section: Prosedur Penelitian 1 Uji Solubilitas Ekstrak Kulit Buahunclassified
“…Nilai PI yang dihasilkan yaitu rata-rata 0,454 yang mengindikasikan keseragaman ukuran nanoemulsi, dimana apabila nilai indeks polidispersitas (PI) semakin kecil maka dapat diartikan ukuran nanoemulsi yang terbentuk semakin seragam. b. Potensial Zeta Nilai potensial zeta yang lebih besar dari (+30) mV atau lebih kecil dari (-30) mV akan stabil secara elektrostatik, sedangkan nilai potensial zeta yang lebih besar dari (+20) mV atau lebih kecil dari (-20) mV akan stabil secara sterik [14].…”
Section: Karakteristik Ukuran Partikel Danunclassified